eCM 2010
DOI: 10.22203/ecm.v020a07
|View full text |Cite
|
Sign up to set email alerts
|

Functional assay, expression of growth factors and proteins modulating bone-arrangement in human osteoblasts seeded on an anorganic bovine bone biomaterial

Abstract: The basic aspects of bone tissue engineering include chemical composition and geometry of the scaffold design, because it is very important to improve not only cell attachment and growth but especially osteodifferentiation, bone tissue formation, and vascularization. Geistlich BioOss ® (GBO) is a xenograft consisting of deproteinized, sterilized bovine bone, chemically and physically identical to the mineral phase of human bone.In this study, we investigated the growth behaviour and the ability to form focal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
0
35
0
4
Order By: Relevance
“…Anorganic bovine bone (ABB) (Bio-Oss, Geistlich, Wolhusen, Switzerland) is a xenograft bone substitute biomaterial widely used as a scaffold to allow osteoblasts migration from the neighboring bone and new bone formation [16][17]. Several studies on ABB have demonstrated Histologically and histomorphometrical that new bone formation takes up to 6 months after grafting alveolar ridge defects [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorganic bovine bone (ABB) (Bio-Oss, Geistlich, Wolhusen, Switzerland) is a xenograft bone substitute biomaterial widely used as a scaffold to allow osteoblasts migration from the neighboring bone and new bone formation [16][17]. Several studies on ABB have demonstrated Histologically and histomorphometrical that new bone formation takes up to 6 months after grafting alveolar ridge defects [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Blood plasma is essential for cell survival as it contains proteins, nutrients, vitamins, hormones and electrolytes. The plasma-proteins are particularly important molecules of the coagulation process able to form the fibrin clot that will serve as a transitory extracellular matrix for cell migration and proliferation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although these signalling pathways have been demonstrated to be mediated by direct binding of the hormone CT to the CTR expressed by osteoclasts [28], the presence of the CTR in osteoblasts still remains unclear and controversial, as well as which signalling cascade is activated by CT [18,29]. It has been reported that there are CTR-mediated effects in osteoblastic cell lines and primary cultures of osteoblast-like cells of rodent [30][31][32], and human [22,29,33] origins; on the other hand, Naot and Cornish showed high levels of CTR-like receptor, but no expression of the CTR, in human primary osteoblasts [24]. The variability of the available data might be dependent on the complexity of the CT/CTR system, the variety of CT-family factors, the several patterns of receptor expression and assembly in cell lines, and the different experimental models used [24].…”
Section: Introductionmentioning
confidence: 99%
“…A opção pela proporção de 1:1 baseou-se em resultados positivos para o processo de reparação óssea e para a estabilidade de implantes com o uso de osso autógeno e Bio-Oss ® (Kim et al 2009;Jensen et al 2012a Avaliações clínicas, radiográficas e histológicas permitem detectar os efeitos positivos do uso combinado de osso autógeno e osso bovino inorgânico sobre a reparação óssea e os índices de sucesso de implantes osseointegráveis (Iezzi et al 2008;Ferreira et al 2009;Kim et al 2009;Galindo-Moreno et al 2010;Jensen et al 2012b;Patel et al 2012). Adicionalmente, métodos in vitro permitem avaliar aspectos morfológicos e moleculares da exposição de células a partículas de osso bovino inorgânico (Trubiani et al 2010;Mladenovic et al 2011), assim como o componente celular dos tecidos neoformados em contato com osso bovino inorgânico in vivo Não se pode descartar a possibilidade de a redução do potencial osteogênico das culturas derivadas do seio maxilar estar diretamente relacionada a uma menor população de células da linhagem osteoblástica presente nos sítios de enxertia no momento de instalação de implantes. Se isso se confirmasse, esse fenômeno tecidual poderia afetar negativamente o processo de formação óssea na região interfacial no período pós-implantação, assim como a remodelação óssea em períodos subsequentes, com potenciais repercussões clínicas, como, por exemplo, as de redução da altura óssea com progressiva pneumatização do seio maxilar (Hatano et al 2004) e do contato osso-implante (Jensen et al 2012a).…”
Section: Atividade De Alpunclassified
“…2004;Araújo et al 2009). Dando mérito a isso, um número de estudos in vitro tem demonstrado efeitos negativos das partículas de OBI na adesão de células osteoblásticas, na proliferação, na expressão gênica, e na formação da matriz óssea mineralizada Herten et al 2009;Bernhardt et al 2011;Trubiani et al 2010).…”
Section: Introductionunclassified